The Influence of Leadership Style, Motivation, and Work Environment on the Employee Performance Productivity of SMES at PT Literindo in Malang City - Meriana Malo; Cakti Indra Gunawan; Noviana Yaniar Suprajitno (International Journal of Management and Business, 2026)
The purpose of this study was to determine the influence of leadership style, motivation, and work environment on the productivity of SME employees at PT Literindo in Malang City, both partially and simultaneously. This type of research is quantitative. The population of this study was all 30 employees at PT Literindo in Malang City, and the sampling technique used total sampling. The instrument used was a questionnaire. Data analysis used multiple linear regression. Hypothesis testing used the t-test (partial) and F-test (simultaneous). The results of multiple linear regression obtained three independent variables have positive regression coefficient values, and the coefficient of determination value isR Squareof 0.949 (the contribution of the influence of the independent variable on the dependent variable is 94.9%). The results of the partial t-test hypothesis test showed that the three independent variables had a t-value of 0.949. count > t tablewith a significance of <0.05 and the results of the F hypothesis test (simultaneous) obtained an F valuecount > Ftablewith a significance value <0.05. Therefore, it is concluded that leadership style, motivation, and work environment have a significant effect on the productivity of SME employees at PT Literindo in Malang City, both partially and simultaneously. PT Literindo's leadership/management is advised to integrate policies targeting these three variables to achieve maximum productivity results. The synergy between strong leadership, high motivation, and a conducive work environment is the main key to maintaining competitive advantage and long-term business growth.